PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODA 2011 – 2015 - Sandra Cicilia Erkanawati (Ma Chung Press, 2018)
The purpose of this study is to test and prove the effect of economic performance disclosure, disclosure of environmental performance and social performance disclosure either partially or simultaneously to the enterprise value as indicated by Economic Value Added. The variables in this study are the Sustainability Report as independent variables consisting of disclosure of economic performance, environmental performance disclosure, and social performance disclosure and corporate value as the dependent variable indicated by Economic Value Added (EVA). The method of analysis used in the study is multiple regression analysis. The population in this study are all mining companies listed on the Indonesia Stock Exchange in the period 2011 to 2015. The sampling technique in this study is one of a kind nonprobability sampling, ie purposive sampling by taking a sample of a mining company based on predetermined criteria, the obtained sample as many as 16 companies. The results showed that the first hypothesis, the hypothesis second and third hypotheses lead to disclosure of economic performance, the disclosure of environmental performance and social performance disclosure on sustainability report has not significant effect on firm value (EVA).